Plasma and milk fatty acid composition as a response to dietary n-3 fatty acids and selenium in periparturient Holstein cows - Mislav Đidara; Marcela Šperanda; Matija Domaćinović; Josip Novoselec; Tomislav Mašek; Mirta Balenović; Nina Poljičak Milas; Neška Vukšić (Mljekarstvo)
Linseed is well known for abundant content of α-linolenic acid why it has been widely used as a source of n-3 fatty acid. Higher ratio of polyunsaturated fatty acids can increase lipid peroxidation. Selenium (Se) plays a key role in antioxidant enzymes and can therefore be regarded for use in attempts focused on protection of fatty acids from oxidation. The organic Se has been shown to have higher bioavailability compared to the inorganic selenium. The aim of this research was to determine the influence of dietary replacement of n-6 with n-3 polyunsaturated fatty acids on plasma and milk fatty acid composition in the dairy cows. The experiment was conducted on 30 dairy Holstein cows in the period from parturition until the 3rd week of lactation. Soybean meal from control (C) group was replaced with grounded linseed in the both experimental (LS and LS+Se) groups. In addition to that, in the 2nd experimental (LS+Se) group sodium selenite from premix was replaced with organic selenium. Blood and milk samples were collected at 21st day of lactation and fatty acids were determined using gas chromatography from it. Feeding dairy cows during transition period with linseed showed a positive impact on milk fatty acid composition by increasing (P<0.05) the proportion of n-3 fatty acids. Proportion of α-linolenic fatty acid increased (P<0.05) in the blood of both groups fed with linseed, but was significant (P<0.05) only in milk of LS+Se group. Such data indicated that the addition of organic selenium acted favourable on α-linolenic fatty acid increase in milk. During early postpartum period addition of linseed in meal of dairy cow’s increased (P<0.05) ratio of oleic acid, but in combination with organic source of selenium this increase was not evident (P>0.05).